Colour design theories and applications - Best, Janet (Cambridge Woodhead Publishing, 2017)
Colour Design: Theories and Applications, Second Edition, provides information on a broad spectrum of colour subjects written by seasoned industry professionals and academics. It is a multidisciplinary book that addresses the use of colour across a range of industries, with a particular focus on textile colouration. Part One deals with the human visual system, colour perception and colour psychology, while Part Two focuses on the practical application of colour in design, including specifically in textiles and fashion. Part Three covers cultural and historical aspects of colour, as well as recent developments, addressing areas such as dyes and pigments, architecture, colour theory, virtual reality games, colour printing, website development, and sustainability. This revised, expanded, and updated edition reflects recent technological developments, and new industry priorities.

Bringing together the science of colouration and the more artistic elements of design, this book supports students, academics, and industry professionals in developing a deep knowledge of colour use. It will also be an important reference for those involved in textile dyeing, design and manufacture.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Color in design; Electronic books